2020
DOI: 10.2147/cmar.s274599
|View full text |Cite
|
Sign up to set email alerts
|

<p>Multidrug Resistance of Gastric Cancer: The Mechanisms and Chinese Medicine Reversal Agents</p>

Abstract: Chemotherapy is the main clinical treatment method of gastric cancer. Multidrug resistance (MDR) has become a common phenomenon with the development of tumors, which alleviates the effect of chemotherapy and makes it difficult to break the bottleneck of survival rate of advanced gastric cancer. Therefore, the exploration of MDR reversal agents for gastric cancer is the focus and also the difficulty of current treatment. Currently, the researches on the mechanisms of drug resistance in gastric cancer have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Although the continuous development of targeted therapy and immunotherapy in recent years has significantly improved the 5-year survival rate of patients with non-small cell lung cancer and the 5-year survival rate of patients with TPS ≥50% after immunotherapy could reach 31.9% ( Reck et al, 2019 ), high treatment costs and adverse reactions also deterred many patients from adhering to those therapies. Chinese patent medicine (CPM), as one of the development products under the theory of traditional Chinese medicine, is composed of natural ingredients and has been proved to be safe and effective ( Huang et al, 2020 ) in enhancing the efficacy of conventional treatments, alleviating adverse reactions ( Chen et al, 2014b ) and improving the patients’ quality of life ( Su et al, 2020 ). CPM is also more cost-effective to most people than western medicine and has been widely used in China.…”
Section: Introductionmentioning
confidence: 99%
“…Although the continuous development of targeted therapy and immunotherapy in recent years has significantly improved the 5-year survival rate of patients with non-small cell lung cancer and the 5-year survival rate of patients with TPS ≥50% after immunotherapy could reach 31.9% ( Reck et al, 2019 ), high treatment costs and adverse reactions also deterred many patients from adhering to those therapies. Chinese patent medicine (CPM), as one of the development products under the theory of traditional Chinese medicine, is composed of natural ingredients and has been proved to be safe and effective ( Huang et al, 2020 ) in enhancing the efficacy of conventional treatments, alleviating adverse reactions ( Chen et al, 2014b ) and improving the patients’ quality of life ( Su et al, 2020 ). CPM is also more cost-effective to most people than western medicine and has been widely used in China.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that surgery, radiotherapy and chemotherapy for GC are ineffective, while TCM treatment has its own advantages. It has great potential in improving immunity of body and alleviating symptoms caused by GC 46 . Although Piwei-Peiyuan Decoction has been widely used in treatment of GC, there is no research on its speci c mechanisms in treatment of GC.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy is one of the important approaches to GC treatment. However, multidrug resistance (MDR) has become a common phenomenon, and it is a main reason for chemotherapy failure, making it difficult to improve the survival rate of patients with advanced GC (3). Therefore, overcoming the MDR of GC to chemotherapy and improving the efficacy of anticancer drugs are key issues in the global medical community.…”
Section: Introductionmentioning
confidence: 99%